The role of training institutions in formalising artisanal and small-scale mining: Paper presented at 11th Zimbabwe International Research Symposium - 16-17 February 2017 - Mamuse, Antony; Mandaza, Edwin Zororo (Research Council of Zimbabwe, 2018)
Artisanal and small scale mining (ASM) is widespread in minerals-rich developing countries including Zimbabwe where it constitutes both a livelihood strategy and an economic development activity. According to case studies in this paper, the ASM sector in Zimbabwe faces challenges of inadequate skills, equipment, health and safety standards, and access to capital and markets which hamper productivity. This paper demonstrates that universities and technical colleges can complement government efforts in enhancing mining productivity and environmental and safety standards of ASM through formalising the sector by rendering appropriate training, support and equipment. Such well-trained and well-equipped miners are likely to undertake formal mining that can attract requisite funding. Mining-related departments can further contribute to formalisation of the sector by empowering graduates to start their own formalised small mining enterprises, by manufacturing and availing affordable mining and mineral processing equipment to the sector, and by undertaking or facilitating resource mapping and evaluation.